Evaluation of grasslands consumed by mother alpacas and tuis (vicugna pacos) in wetlands in the dry season, Yauyos, Peru - Quispe Ramos, Rolando Zócimo (2021)
The research was carried out in the alpaca production unit of the Tomas Peasant Community, of the Lima Region, with the aim of identifying the floristic component of the pasture of a wetland area in the dry season of the year and the species that were most consumed by alpacas. Previously, the floristic inventory of 5 hectares of pasture was carried out and 10 mother alpacas and 10 tuis alpacas were assigned. During the study period, stool samples were taken to evaluate the diet by the microhistological method. The chemical components of the six main species of grasses most consumed were analyzed. In the initial inventory 36 species were found, of which the most consumed were 10 that made up approximately 80% of the diet. Chemical analysis shows a crude fiber content in a range between 66,23 to 77,24%, crude protein between 2.49 to 5,21% and vitamin A between 0,08 to 0,37 mg / 100g. The contribution of the present is to identify the species of pasture most consumed by alpacas tuis and mothers, in order to take care in their conservation.